2001
DOI: 10.1097/00003246-200102000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Impaired target site penetration of β -lactams may account for therapeutic failure in patients with septic shock

Abstract: The results of the present study demonstrate that in septic shock patients, piperacillin concentrations in the interstitial space may be subinhibitory, even though effective concentrations are attained in plasma. The lack of success of antimicrobial therapy in these patients thus might be attributable to inadequate target site penetration of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
168
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(186 citation statements)
references
References 28 publications
14
168
2
2
Order By: Relevance
“…Our PD data resembled the data of others, suggesting that the probability of target attainment (probability of reaching fT.MIC564 mg/ml>50%) was not 100% (10,19,20).…”
Section: Discussionsupporting
confidence: 85%
“…Our PD data resembled the data of others, suggesting that the probability of target attainment (probability of reaching fT.MIC564 mg/ml>50%) was not 100% (10,19,20).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, however, the proportionality factor was necessary to allow the prediction of free tissue concentrations based on plasma PK parameters, indicating that infection caused physiological changes in muscle such as increase in vascular permeability leading to increase in protein concentration at the infection site, increase in tissue temperature and pH alterations that would ultimately lead to an around 30% decrease in free interstitial levels of PIP. Joukhadar et al 10 studied the tissue penetration of piperacillin in skeletal muscle and s.c. adipose tissue in patients with septic shock, using microdialysis, and observed that the free levels of piperacillin in these situations were 5-10 times lower than the corresponding free plasma concentrations, indicating the infectious process changed the penetration of this antimicrobial, reducing its clinical effectiveness. The difference between this study and that reported by Joukhadar et al is that in the present one the animals had a localized infection instead of a septic shock that definitively alters body homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have demonstrated that infection changes the physiological characteristics of the infected tissue due to the inflammatory process developed by host aiming to eliminate the invasive organism, as observed in soft tissue infections, septic shock, pneumonia or vascular alterations associated to diabetes. [9][10][11][12] In this context, it is not always possible to predict the antimicrobial-free fraction at the site of infection, based on the microdialysis data obtained in healthy tissue or unbound plasma levels.…”
Section: Introductionmentioning
confidence: 99%
“…Despite tremendous investments in new treatments, arresting poor clinical outcomes has been a global challenge [2]. For -lactam antibiotics, which are the mainstay of therapy in severely ill patents, emerging evidence suggest that poor antibiotic exposure is a potential cause of poor clinical outcomes [3][4][5].…”
Section: Introductionmentioning
confidence: 99%